Reclus, a colonialist? - Axel Baudouin (Unité Mixte de Recherche 8504 Géographie-cités, 2003)
The geographer and anarchist Elisée Reclus is considered as one of the foremost anti colonialists of his time. When analyzing his writings, several authors were unable to ignore the fact that even when he criticized colonization methods, Reclus was nevertheless an advocate of colonization. This paper attempts to review the issue by using archive material and publications and by looking once more at Elisée Reclus’s stance in the second half of the 19th century, together with other critics of colonial events from other political backgrounds. In spite of his criticism and humanism, it is clearly documented that throughout his life, Reclus was a dedicated partisan of colonization, even if his view was a “democratic” and somewhat idealized version.Reclus’s position appears logical when related to commonly held western beliefs, shared by the radical left socialists and anarchists, that the “civilized world” had a mission to fulfill in the rest of the world. The colonial issue can be seen as a major component of the on-going globalization, already at work for many centuries.